Electromagnetic wave diffraction on rectangular waveguides cascaded junction - Гнатюк, М.А.; Морозов, В.М.; Марченко, С.В. (Radiotekhnika, 2019)
The approach within the overlapping partial domain method is offered. The electromagnetic wave diffraction problem on cascaded junction of rectangular waveguides is considered. Frequency dependences of the reflection coefficient magnitude are obtained for different values of the intermediate waveguide longitudinal size.